Towards using a generic robot as training partner: off-the-shelf robots as a platform for flexible and affordable rehabilitation - Sørensen, Anders Stengaard; Savarimuthu, Thiusius Rajeeth; Nielsen, Jacob; Schultz, Ulrik Pagh (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
In this paper, we demonstrate how a generic industrial robot can be used as a training partner, for upper limb training. The motion path and human/robot interaction of a non-generic upper-arm training robot is transferred to a generic industrial robot arm, and we demonstrate that the robot arm can implement the same type of interaction, but can expand the training regime to include both upper arm and shoulder training. We compare the generic robot to two affordable but custom-built training robots, and outline interesting directions for future work based on these training robots.